Environmental antimicrobial resistance and its drivers: a potential threat to public health. (December 2021) - Samreen,; Ahmad, Iqbal; Malak, Hesham A.; Abulreesh, Hussein H.
Highlights: Antibiotic-resistant bacteria in the environment may reach humans via different transmission routes. These bacteria may transmit their antimicrobial resistance genes to humans via the food chain. Judicious antimicrobial use in livestock/veterinary sectors and restricting antimicrobials as growth promoters is required. Various drivers of antimicrobial resistance (AMR) need to be studied for their relative importance in AMR dissemination. Filling knowledge gaps as well as interconnected national action plans may help in managing the challenge of AMR. ABSTRACT: Imprudent and overuse of clinically relevant antibiotics in agriculture, veterinary and medical sectors contribute to the global epidemic increase in antimicrobial resistance (AMR). There is a growing concern among researchers and stakeholders that the environment acts as an AMR reservoir and plays a key role in the dissemination of antimicrobial resistance genes (ARGs). Various drivers are contributing factors to the spread of antibiotic-resistant bacteria and their ARGs either directly through antimicrobial drug use in health care, agriculture/livestock and the environment or antibiotic residues released from various domestic settings. Resistant micro-organisms and their resistance genes enter the soil, air, water and sediments through various routes or hotspots such as hospital wastewater, agricultural waste or wastewater treatment plants. Global mitigation strategies primarily involve the identification of high-risk environments that are responsible for the evolution and spread of resistance. Subsequently, AMR transmission is affected by the standards of infection control, sanitation, access to clean water, access to assured quality antimicrobials and diagnostics, travel and migration. This review provides a brief description of AMR as a global concern and the possible contribution of different environmental drivers to the transmission of antibiotic-resistant bacteria or ARGs through various mechanisms. We also aim to highlight the key knowledge gaps that hinder environmental regulators and mitigation strategies in delivering environmental protection against AMR.